The Criminal Liability of Corporations as Crime Perpetrators - Evi Djuniarti (Jurnal Penelitian Hukum De Jure, 2021)
In terms of handling corporate crimes that culminate in "sentencing" or "giving punishment", corruption is referred to as a crime that has caused damage to life. However, this is not mentioned much in criminal law studies. In addition to sentencing, corporations that committed corruption must also return corporate assets to the state. This needs to be considered according to the philosophy of nature aequum est neminem cum alterius detrimento et injuria fieri locupletiorem. This philosophy means that no one can enrich themselves at the expense and suffering of others. This philosophy changes the source of this doctrinal principle, namely crime does not pay or crime shall not pay into an expression of resistance to crime perpetrators so that they cannot enjoy the results of the crime they committed. The statement of the problem in this paper is how is the philosophy of sentencing corporations that are perpetrators of corruption? This research used secondary data through literature study in the form of laws and descriptive analysis. The imposition of a criminal fine creates implications and juridical problems for corporations that committed corruption. The recommendation of this paper is to build an ideal model of sentencing corporation based on justice.